2014
DOI: 10.1080/01932691.2013.844704
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Priority Pollutant 4-Nitrophenol from Water by Emulsion Liquid Membrane: Emulsion Stability, Effect of Operational Conditions and Membrane Reuse

Abstract: This work aims to the extraction of the priority pollutant 4-nitrophenol (4-NP) from water by emulsion liquid membrane (ELM). Liquid membrane consists of a diluent (hexane) and a surfactant (Span 80). Sodium carbonate solution was used as internal aqueous phase. Effects of important experimental conditions governing the stability of the W/O emulsion were investigated. Influence of operating parameters that affects the permeation of 4-NP such as surfactant concentration, emulsification time, sulfuric acid conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 28 publications
(22 reference statements)
1
11
0
Order By: Relevance
“…These results are also in line with those of Chaouchi and Hamdaoui. 29 Thus, the agitation speed of 300 rpm was chosen to obtain a stable emulsion in this study.…”
Section: Resultsmentioning
confidence: 99%
“…These results are also in line with those of Chaouchi and Hamdaoui. 29 Thus, the agitation speed of 300 rpm was chosen to obtain a stable emulsion in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Through a review of previous studies, it was found that the optimum speed for each research varied based on the working conditions and the extracted pollutant and its concentration, where Salman et al [7] said that the best speed is 12,700 within 10 min of lead with a concentration pouring to 200 ppm, and 20000 rpm at 4 min in another study Chaouchi et al [37] .…”
Section: Effect Of Homogenizer Speed On System Stability and Extraction Efficiency Of Lead Copper And Cadmiummentioning
confidence: 99%
“…The effect of the volume ratio of emulsion to the external phase on the extraction efficiency was studied. Experiments were carried out using the following experimental conditions [19,20]: initial 4-NP concentration of 25 mg/L; external phase (4-NP solution) volume of 250 mL; volume ratio of internal phase to organic phase of 1/1; emulsification time of 4 min; stirring speed of 300 rpm; Span 80 concentration of 3% (w/w); internal phase concentration (Na 2 CO 3 ) of 0.1 N; sulfuric acid concentration in the feed phase of 0.1 N; and hexane as diluent. The obtained results are shown in Fig.…”
Section: Effect Of Treatment Ratiomentioning
confidence: 99%